Commercializing blockchain : strategic applications in the real world - Welfare, Antony (Wiley, 2019)
"Commercializing Blockchain: Strategic Applications in the Real World is written as a practical guide to blockchain and how it can be used to transform governments, businesses, enterprises and communities, bringing benefits such as increased trust, transparency, security (cryptography), quality, certainty, reduced costs and efficiency. Beginning with a brief overview of the technology, the major part of the book consists of real-use case studies of blockchain, drawn from the author's extensive experience with Oracle, UCL, the UK government, Blockchain Live and many other sources. These cases illustrate how blockchain can be deployed to manage complex, real world issues such as financial transactions, tokenization, identity management, loyalty, gift cards, warranty management, refunds management, supply chain transparency, global shipping and freight, improved sourcing, certification and authentication, inventory management, traceability, provenance, and counterfeiting. In addition to the use cases there is a continued fictional retail example called "Antony Stores Group", a complex retailer suffering with many issues to which blockchain technology can be applied"--